Efforts to Improve Student Learning Outcomes on Asmaul Husna Material Through Wordwall Media - Muhaiminah; Imron, Ali; Herningtyasari, Gadis (Journal of Asian Primary Education (JoAPE), 2024)
This study aims to improve the learning outcomes of fourth-grade students on the topic Asmaul Husna material through Wordwall media at UPTD SD Negeri 2 Maddukkelleng. This Classroom Action Research/Penelitian Tindakan Kelas was conducted in two cycles, each consisting of planning, implementation, observation, and reflection phases. The results showed that Wordwall media could improve students' learning outcomes, as evidenced by an increase in the class average score from cycle I to cycle II and improved student activity and participation during the lessons. Based on these findings, Wordwall can be an effective alternative teaching media for Islamic Education subjects.